Effects of rural collective economy policy on the common prosperity in China: based on the mediating effect of farmland transfer - Jiang, Fan; Jiang, Yadan; Peng, Jiquan; Lv, Yangqin; Wang, Weiwei; Zhou, Ziming (Frontiers in Environmental Science, 2023)
The rural collective economy plays a crucial role in achieving the common prosperity of farmers, revitalizing the countryside, and modernizing agriculture in China. This paper analyses the impact and internal mechanism of the policy on the level of common prosperity, using provincial panel data from China from 2011 to 2020. Additionally, it investigates whether the rapid development of the rural collective economy takes into account both economic growth and income distribution. The findings demonstrate that the policy significantly enhances the common prosperity of farmers and rural areas. These conclusions remain valid even after considering the endogeneity problem and conducting robustness tests using the time-varying difference-in-differences (DID) model. Furthermore, the intermediary effect model reveals that the increase in the rate of farmland transfer and the proportion of scale operation play crucial roles in transmitting the benefits of the policy to achieve common prosperity. The result of the heterogeneity analysis indicates that the marginal decline of policy effect has a greater impact on the enhancement of rural collective economy in the less developed provinces of the central and western regions in China, compared to the developed provinces of the eastern region. These findings have targeted policy significance for promoting the sustainable development of agricultural and rural areas.